Pengaruh Penggunaan Berbagai Jenis Pakan Terhadap Pertumbuhan Tukik Penyu Hijau (Chelonia mydas) - Adi Wibowo, Yulius Basuki; Sunaryo, Sunaryo; Ambariyanto, Ambariyanto (977-2407769)
Indonesia is known as archipelagis country which high marine biodiversity, includ turtle. there are six species of sea turtles are found In Indonesia i.e. Green turtle (Chelonia mydas), Hawksbill turtle (Eretmochelys imbricate), Dark turtle (Lepidochelys olivacea), leatherback turtle (Dermochelys coriacea), Natator depressa and Carreta Carreta. The green turtles (Chelonia mydas) were the most intensively exploited and classified in endangered species. One the efforts to protect sea turtle population is by realism turtle hetcling to the sea. The research was conducted on September 2009 in Pangumbahan beach, Sukabumi. The method used in this study is an experimental using a Completely Randomized Design (CRD) with 3 treatments and 3 replications. The results showed that there was symulicat different on the growth of Green Turtle hatchlings that were given different type of feed (p = 0.021 for hatchling weigth), (p = 0.013 for hatchling length), and (p = 0.032 for hatchling width). Further analysis (Tukey’s test) showed that rebon shrimp feed give effect on the growth of Green Turtle hatchling eiter based on weigth, length or width of the hetchling.